AKTIVITAS REPELLENT FORMULASI SEDIAAN SPRAY KOMBINASI MINYAK ATSIRI SERAI (Cymbopogon winterianus), DAUN KEMANGI (Ocimum basilicum) DAN NILAM (Pogostemon Cablin) BESERTA UJI PREFERENSINYA - Faikah Dyah Utami; Arif Budi Setianto (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Plants that are played as mosquito repellents, one of which is plants that contain essential oils, such as lemongrass, basil and patchouli. As an effort to make it easier to use, this research will make a spray repellent preparation with a combination of active ingredients from essential oils of lemongrass, basil and patchouli. The research methods included making a spray repellent using essential oils of lemongrass, basil, patchouli every 0.1 ml (5 concentrations %), 0.2 ml (10% concentration), 0.3 ml (15% concentration) and the additives 1ml Propylene glycol and 5 ml 96% Ethanol which functions as a solvent. The experiment used five treatments, namely: Negative control (Kn), Formula A (0.1ml), Formula B (0.2ml), Formula C (0.3ml), and Positive Control (Kp). The parameters tested included pH test, patch test, organoleptic, specific gravity, emulsion stability, preference and percentage of protective power. The protective power test was carried out 10 times from each treatment for 6 hours of observation (0-1 hours, 1-2 hours, 2-3 hours, 3-4 hours, 4-5 hours and 5-6 hours). The results showed that the best spray expulsion treatment was formula B with a concentration of 10% (0.2 ml)